Public happiness and its causes in Malaysia / Mahadzir Ismail and Jamilah Laidin - Ismail, Mahadzir; Laidin, Jamilah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
This paper seeks to determine the main causes of public happiness in Malaysia. Happiness scores were obtained using Oxford Happiness Questionnaire. Four factors were selected namely economic status, life expectancy, religiosity and social capital. The study found that all four causes are significant and religiosity is the most dominant factor.